Immunological Approach to Lung Cancer Part A: Immunology of Lung Cancer - Ilhan, Fulya (Bentham Science Publ, 2013)
Immune system direct or indirectly can be effective in the movement of cancer. A lot of moleculer study was made for explaining immune mechanism of lung cancer. Different immune mechanisms and tumour factors relating the existence mechanism of the disease are examined in this manuscript.
Keywords: Lung cancer; immunology; immune mechanism; CTLA-4; PD-1